Experimental and quantum chemical analysis of 2-amino-3-((4-((S)-2-amino-2-carboxyethyl)-1H-imidazol-2-yl)thio) propionic acid as new and green corrosion inhibitor for mild steel in 1 M hydrochloric acid solution - Haque J.; Srivastava V.; Verma C.; Quraishi M.A. (My University, 2025)
A new corrosion inhibitor namely, 2-amino-3-((4-((S)-2-amino-2-carboxyethyl)-1H-imidazol-2-yl)thio)propionic acid (AIPA) has been synthesized and its inhibition action on corrosion of mild steel in 1 M HCl has been investigated using Electrochemical impedance spectroscopy (EIS),Potentiodynamic polarization, Scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX) and Atomic force microscopy(AFM) methods. The results obtained from above methods reveal that AIPA is an excellent inhibitor. It gives a maximum inhibition efficiency of 96.52% at 0.456 mM/L (125 ppm; 125 mg L− 1) and inhibits corrosion by adsorbing at the mild steel surface. Polarization study suggested that AIPA acts as mixed type inhibitor with some cathodic predominance. SEM and AFM analyses showed improved morphology of the mild steel surface in presence AIPA. Quantum chemicals parameters such as EHOMO, ELUMO, ΔE, global hardness and softness, electronegativity and fraction of electron transfer (ΔN) were calculated using DFT method to correlate the electronic properties with the adsorption and inhibition behavior of AIPA. © 2016 Elsevier B.V.